A method for measuring the inertia properties of a rigid body using 3-URU parallel mechanism. (15th May 2019) - Liu, Yu; Liang, Bin; Xu, Wenfu; Wang, Xueqian
Highlights: A new method of measuring all inertial properties using 3-URU parallel mechanism is presented. The forward solution of the parallel mechanism gives kinematics required by parameter identification. The developed measurement device only includes three angle encoders and three tensile force sensors. The experiment shows that the method has the advantages of high precision, short time and low cost. Abstract: Using the 3-URU parallel mechanism a new method of measuring all inertial properties is presented. After a rigid body is fixed on the mobile platform of the mechanism, the method can firstly measure its mass, and then its center of mass and inertia tensor. Its principle is based on the general nonlinear motion equation, and the angular velocity and acceleration of the measured rigid body required for the principle is obtained by using the forward kinematics of the parallel mechanism. The forward solution is derived according to the recorded joint angles, the adopted Newton-Raphson plus least square algorithm guarantees the stability of the solution of a highly nonlinear redundant equation set. Next, polynomial fitting of the pose (position and orientation) of the mobile platform is performed, and then the first and second derivatives are evaluated for the angular velocity, linear acceleration and angular acceleration. The presented technique only consists of three angle encoders and three tensile force sensors without any other inertial measurement units (such as gyro and acceleration sensors), which is economical. The measurement method is verified by measuring two different rigid bodies (symmetrical and asymmetrical), and satisfactory results have been obtained for both the measurement time and the measurement accuracy. The presented method is a passive method relying on the gravitational field, so it does not require any excitation device. It can be applied to automobile, aviation, aerospace and other industries.